Genetic variation for total carotene, iron, and zinc contenet in maize genotypes and cassava clones - Maziya-Dixon, B.B.; Kling, J.G.; Menkir, A.; Dixon, A. (SAGE Publications, 2000)
Deficiencies of vitamin A, iron, and zinc are widespread in sub-Saharan Africa, where the diets are mainly plant-based and the intakes of animal products are low. The overall objective of this investigation was to determine the extent of genetic variation of these micronutrients in 16 yellow-seeded improved maize varieties, 109 maize inbred lines (60 from mid-altitude and 49 from lowland/savannah agroecologies), and 162 cassava clones resistant to the cassava mosaic disease. The yellow-seeded improved maize varieties were analysed for physical and chemical characteristics and total carotene content; the maize inbred lines and cassava clones were analysed for iron and zinc content. The results showed statistically significant and large genotypic differences in total carotene content among the 16 yellow-seeded improved, open-pollinated maize varieties. The total carotene content ranged from 143 to 278 μg/g. Significant genotypic variation was also observed for iron and zinc concentrations in maize inbred lines and cassava storage roots. Iron concentration ranged from 15 to 159 ppm for midaltitude and from 14 to 134 ppm for lowland maize inbred lines; zinc concentration ranged from 12 to 96 ppm for mid-altitude inbreds and from 24 to 96 ppm for lowland inbred lines. For cassava storage roots, the range was 4 to 95 ppm for iron and 4 to 18 ppm for zinc. A strong and positive relationship was observed between iron and zinc concentrations for both mid-altitude and lowland maize inbred lines, but this relationship was weak for the cassava clones. The potential exists for improving carotene, iron, and zinc contents in maize and cassava genotypes through plant-breeding.